Price adjustment under the Table: Evidence on Efficiency-Enhancing Corruption - Daniel Levy (European Journal of Political Economy, 2007)
Based on first-hand account, this paper offers evidence on price setting and price adjustment mechanisms that were illegally employed under the Soviet planning and rationing regime. The evidence is anecdotal, and is based on personal experience during the years 1960–1971 in the Republic of Georgia. The description of the social organization of the black markets and other illegal economic activities that I offer depicts the creative and sophisticated ways that were used to confront the shortages created by the inefficient centrally-planned command economic price system with its distorted relative prices. The evidence offers a glimpse of quite explicit micro-level evidence on various types of behavior and corruption that were common in Georgia. Rent-seeking behavior, however, led to emergence of remarkably well-functioning and efficiency-enhancing black markets. The evidence, thus, underscores once again the role of incentives in a rent-seeking society.
Keywords: B14; D30; D73; E64; H26; H40; K42; O17; P20; P26; Z13; 330; Corruption; Black Market; Bribe; Price System; Distorted Relative Prices; USSR; Command Economy; Price Controls; Efficiency